HUBUNGAN STATUS GIZI, LINGKAR PINGGANG, DAN PROFIL LIPID TERHADAP HIPERTENSI PADA USIA PRODUKTIF BERPENGHASILAN RENDAH - Kumala, Meilani; Lontoh, Susy Olivia; Novendy, Novendy (Universitas Tarumanagara, 2021)
Background: The prevalence of hypertension in the world today increases year by year. Monitoring data of non communicable diseases (NCD), 2017 shows that the number and risk of death for Indonesian people in productive age is quite high. Research on the relationship between risk factors and hypertension in low-income productive age communities in Indonesia has not been widely studied. Objective: This study aims to determine the relationship between nutritional status, waist circumference (WC) and lipid profile with hypertension in people of low income productive age. Methods: The design of this study was cross sectional. Identity data were collected through interview, blood pressure, anthropometry, waist circumference data were obtained by measuring and blood lipid profile, fasting blood sugar data were carried out by laboratory test. The data that had been obtained were tested using Fisher’s exact test. Results: As many as 50% of 62 subjects had hypetension, 38.7% of subjects had overweight, 33,87% of subjects had obesity and 61.9% of subjects had WC above normal or including central obesity. As many as 37.1% of subjects had hypercholesterolemia, 90.3% had low density lipoproteinemia (LDL) above normal, 16.1% of subjects had high density lipoproteinemia (HDL) below normal and 22.6% of subjects had hypertriglyceridemia. The results of Fisher's exact test showed that there was no relationship between nutritional status, WC and lipid profiles with hypertension. The prevalence odds ratio (POR) showed that subjects with over nutrition and obesity have a 1.63 times risk of developing hypertension; subjects with central obesity had a 1.73 times risk of developing hypertension; subjects with hypercholesterolemia had a 2.7-fold risk of developing hypertension and subjects with high LDL had 2.15 times the risk of developing hypertension, while POR of HDL and triglycerides showed a neutral value or not a risk factor for hypertension. Conclusion: Nutritional status, WC, lipid profile have no relationship with hypertension in low-income productive age people in Indonesia. Based on the POR, it was found that obesity, WC, cholesterol and LDL were risk factors for hypertension, whereas triglycerides and HDL did not affect the incidence of hypertension Keywords: nutritional status; waist circumferences; lipid profile; productive age; low income AbstrakLatar Belakang: Pevalensi hipertensi di dunia dewasa ini meningkat dari tahun ke tahun. Data monitor kemajuan penyakit tidak menular (PTM), 2017 menunjukkan bahwa angka dan risiko kematian masyarakat dengan usia produktif di Indonesia cukup tinggi.Penelitian hubungan faktor risiko terhadap hipertensi pada masyarakat usia produktif berpenghasilan rendah di Indonesia belum banyak dikaji lebih dalam. Tujuan: Penelitian yang dilakukan untuk mengetahui hubungan status gizi, lingkar pinggang (Lpi) dan profil lipid dengan hipertensi pada masyarakat usia produktif berpenghasilan rendah. Metode: Desain penelitian ini adalah potong lintang. Data identitas dikumpulkan melalui wawancara, data tekanan darah, antropometri, lingkar pinggang diperoleh dengan melakukan pengukuran dan data profil lipid darah, gula darah puasa dilakukan dengan pemeriksaan laboratorium. Data yang telah diperoleh, diuji menggunakan uji Fisher’s exact. Hasil: Sebanyak 50% dari 62 subjek mengalami hipertensi, 38,7% subjek mempunyai status gizi berlebih, 33,9% subjek termasuk obesitas dan 61,9% subjek mempunyai Lpi di atas normal atau obesitas sentral. Sebanyak 37,1% subjek mengalami hiperkolesterolemia, 90,3% mempunyai low density lipoproteinemia (LDL) di atas normal, 16,1% subjek mempunyai high density lipoproteinemia (HDL) dibawah normal dan 22,6% subjek mengalami hipertrigliseridemia. Hasil uji Fisher’s exact menunjukkan tidak terdapat hubungan antara status gizi, Lpi dan profil lipid dengan hipertensi. Prevalence odds ratio menunjukkan subjek dengan status gizi berlebih dan obesitas mempunyai risiko 1,63 kali mengalami hipertensi; subjek dengan obesitas sentral mempunyai risiko 1,73 kali mengalami hipertensi; subjek dengan hiperkolesterolemia mempunyai risiko 2,7 kali mengalami hipertensi dan subjek dengan LDL yang tinggi mempunyai risiko 2,15 kali mengalami hipertensi, sedangkan POR HDL dan trigliserida memperlihatkan tidak merupakan faktor risiko hipertensi. Kesimpulan: Status gizi, Lpi, profil lemak darah tidak mempunyai hubungan dengan kejadian hipertensi pada masyarakat usia produktif berpenghasilan rendah. Gizi lebih dan obesitas, Lpi, kolesterol dan LDL merupakan faktor risiko kejadian hipertensi sedangkan, triglieserida dan HDL tidak memengaruhi kejadian hipertensi.